In Situ Stress and Pore Pressure in the Deep Interior of the Nankai Accretionary Prism, Integrated Ocean Drilling Program Site C0002. Issue 19 (9th October 2017) - Kitajima, Hiroko; Saffer, Demian; Sone, Hiroki; Tobin, Harold; Hirose, Takehiro
Abstract: Strength and slip behaviors of subduction megathrusts are controlled by the physical properties and stress state not only of the fault zones themselves but also the adjacent wall rocks in overriding and subducting plates. In the Nankai Trough, a 3 km deep riser borehole at Integrated Ocean Drilling Program Site C0002 was drilled into the Kumano fore‐arc basin and the underlying accretionary prism. We quantify the full in situ stress tensor and pore pressure at Site C0002 by integrating drilling data, geophysical logging, and downhole measurements using empirical relations that describe sediment compaction behavior as a function of loading path. The Kumano Basin is loaded in uniaxial vertical strain conditions, whereas the prism below is loaded with greater differential stress, has a modestly elevated pore pressure, and lies in a strike‐slip faulting regime. This can be reconciled with slip on the megathrust fault if the horizontal stresses vary with time or depth and/or if shear stress along the megathrust is low. Key Points: The full in situ stress tensor and pore pressure are quantified at a 3 km deep borehole within the Nankai accretionary prism The accretionary prism is loaded with greater differential stress and a modest overpressure and lies in a strike‐slip faulting regime The in situ stress and pore pressure largely vary with depth; the depth‐varying conditions can affect the strength of megathrusts